"I'm Still Surviving": Oral Histories of Women Living with HIV/AIDS in Chicago. (9th April 2018) - Brier, Jennifer
Abstract: This article recounts the creation of an oral and public history project, "I'm Still Surviving, " which seeks to document, write, and display a women's history of HIV/AIDS in the United States. Using feminist oral history and decolonial methods for both the collection and interpretation of oral history narratives, the project grounds and amplifies self-determination by women living with HIV/AIDS as it decenters the notions that academic historians are the experts on the history of the epidemic. The goal of the project is to collaborate with women living with HIV/AIDS so that together we can produce a decolonized public history of women's experiences of surviving HIV/AIDS.